Transformation of Vocational Learning Through Augmented Reality: An Innovative Concept for Strengthening Visual Skills in Culinary Vocational Schools - Fitriyana Fitriyana; Didik Nurhadi (Green Publisher Indonesia, 2025)
The development of digital technology in the era of the Industrial Revolution 4.0 requires vocational education to adapt to more interactive, contextual, and competency-based learning approaches. This study addresses critical challenges in Culinary Vocational High Schools (SMK), where students demonstrate low visual-spatial skills in understanding complex culinary techniques such as precision cutting, artistic plating, and creative decorating. This article proposes the concept of Augmented Reality (AR)-based learning as a vocational education transformation strategy that integrates digital learning experiences with real-world practices. The study employs a comprehensive conceptual analysis methodology, synthesizing theoretical frameworks from the Cognitive Theory of Multimedia Learning and Experiential Learning Theory with contemporary research on AR applications in vocational education published between 2020 and 2025. The proposed conceptual model, AR-based Experiential Culinary Learning (ARECL), combines the principles of the Cognitive Theory of Multimedia Learning and Experiential Learning Theory to create an immersive, collaborative, and hands-on experience-based learning process. Through this integrated theoretical approach, the ARECL model is expected to significantly enhance students' visual-spatial competencies, increase intrinsic learning motivation through interactive engagement, strengthen procedural skill development, and establish an adaptive vocational learning ecosystem that effectively prepares students for the dynamic challenges of the modern culinary industry. The implications of this conceptual framework extend to curriculum development, teacher professional development programs, and strategic industry-education partnerships that can collectively transform vocational education delivery in the digital age.